ANALISIS C-ORGANIK, NITROGEN DAN C/N TANAH PADA LAHAN AGROWISATA BEKEN JAYA DI KABUPATEN KUANTAN SINGINGI - Trinop Sagiarti; Deno Okalia; Gusti Markina (Fakultas Pertanian - UMJ, 2020)
Soil fertility determined by land management . Land use in the farmers to Beken Jaya in Kuantan Singingi has been going on for seven years to technique fertilizing not recommended, so it is important to knew soil chemical characteristic are now being to sustainable agriculture.This research in the soil samples uses the method purposive random sampling in 15 points gas drilling land as deep as 20 cm.Parameter examined is pH , C-organic , N-total , N-available and ratio C / N. All the data compared to table criteria of the chemical properties the ground by LPT 1993. Based on the results of the soil analysis in Agrowisata Beken Jaya can be concluded features chemical pH 5,88 -6,41 ( criteria midle acid ) , C-organik 0.25 % - 1,18 % ( criteria very low until low ) , N-total 0,30 -1,16 % ( criteria moderate to very high ), and C/N 0,24-3,97 (criteria very low)